Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4148/1936-0487.1094
|View full text |Cite
|
Sign up to set email alerts
|

Defining Homelessness in the Rural United States

Abstract: Rural homelessness in the United States is an understudied phenomenon. Among those studies which do address the issue, there exists no uniform or consistent definition for rural homelessness. In this review of the literature, we look at rural homelessness and consolidate the literature into four main groups based on the definitions currently in use. We recommend a comprehensive definition for rural homelessness that looks at this phenomenon on a spectrum of needs, populations, and periodicity. We further recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The small group of individuals known to police and community leaders were highly visible in the community but did not represent this range of individuals struggling with access to a suitable shelter. This is consistent with a growing body of literature demonstrating the most consistent feature of rural homelessness is its invisibility (Carpenter‐Song et al., 2016; Gibbons et al., 2019; Kauppi et al., 2017; MacDonald & Gaulin, 2019; Waegemakers Schiff et al., 2016; Yousey & Samudra, 2018). The lack of infrastructure in a rural setting, including shelters and warming centres, means many people facing homelessness rely on informal networks and strategies that hide them from public view.…”
Section: Discussionsupporting
confidence: 84%
“…The small group of individuals known to police and community leaders were highly visible in the community but did not represent this range of individuals struggling with access to a suitable shelter. This is consistent with a growing body of literature demonstrating the most consistent feature of rural homelessness is its invisibility (Carpenter‐Song et al., 2016; Gibbons et al., 2019; Kauppi et al., 2017; MacDonald & Gaulin, 2019; Waegemakers Schiff et al., 2016; Yousey & Samudra, 2018). The lack of infrastructure in a rural setting, including shelters and warming centres, means many people facing homelessness rely on informal networks and strategies that hide them from public view.…”
Section: Discussionsupporting
confidence: 84%
“…But social connectedness and access to social opportunities in rural communities look different from those experienced in urban settings. Though the United States is an increasingly urban-centric society, rural communities encompass more than 70% of the country (United States Census Bureau, 2019; Yousey & Samudra, 2018). If relationships between people are reciprocal and dynamic, it stands to reason that people living in rural communities may have less opportunity for general well-being because they experience decreased access to resources and opportunities for social interaction (Fleisch Marcus et al, 2017).…”
Section: Rural Poverty Contextmentioning
confidence: 99%
“…Furthermore, Weeks (2018) found that people living in rural areas in the United States have experienced a decline in life expectancy compared to the general positive trend in national life expectancy. This trend may indicate that rural issues impact wellbeing, leading to an increase in social isolation, lack of access to healthcare, food insecurity, transportation challenges (Weirich & Benson, 2019), housing inadequacy (Yousey & Samudra, 2018), as well as poor health behaviors and attitudes, higher smoking rates, mental health stigma (Weeks, 2018) and the ongoing opioid epidemic.…”
Section: Rural Poverty Contextmentioning
confidence: 99%
“…Studies indicate that people living in rural places are 2.3 times more likely to suffer from homelessness-related difficulties than their counterparts in urban locations (Rollinson & Pardeck, 2018). Additionally, rural homelessness is more prevalent in agricultural areas whose economies depend on declining extractive industries such as fishing, mining, or timber (Yousey & Samudra, 2018). Rural homelessness is further amplified by the more extended periods of unemployment, low wages, and fewer job opportunities (Fitzpatrick, 2012).…”
Section: Introductionmentioning
confidence: 99%